ELISITASI PENINGKATAN PRODUKSI AJMALISIN OLEH KALUS Catharantus roseus (L.) G. Don. - Silalahi, Marina (BERITA BIOLOGI, 2010)
An experiment to study the effect of soft fraction derived from Saccharomyces cerevisiae (Hansen) to elicit ajmalicine production by Catharanthus roseus (L.) G. Don. callus cultures has been conducted. Callus were induced from leaf segment and grew on Zenk medium supplemented with 2,5 x l0M NAA dan 10 M BAP respectively. Callus on the third subculture level were elicited with soft fraction derived from S. cerevisiae. The following concentrations of elicitor tested were 0, 0,5, 1,0 and 2,5 % (g/v), and the harvesting times were 0, 18, 36 and 72 hour respectively. Influence of elicitor to production of ajmalicine by the callus were analyzed qualitatively and quantitatively by using high performance liquid chromatography (HPLC). A significant increasing of ajmalicine content in the callus (303,475 Â± 5,602 ug/gDW) was achieved by addition of elicitor of 0,5 % (g/v) after 36 hour. This study showed a significant increase of ajmalicine production in C. roseus callus cultures after being challenged with elicitor derived from S. cerevisiae i.e. 69,334%.